Characterisation of effective antifungal Lactobacillus strain isolated from Chilika curd - Kumar, Hitesh; Kumar Nanda, Dhiraj; Gaare, Manju; Singh, Rameshwar (Indian Journal of Dairy Science, 2024)
In this study different strains of Lactobacilli isolated from Chilika curd, (fermented milk product native to the Chilika region of Odisha, India) were assessed for their antifungal activity. Limosilactobacillus fermentum C-14 was shown to have the strongest inhibitory activity against tested yeast and mold cultures. This antifungal activity of cell free supernatant (CFS) Lb-C-14 was found to be stable at high temperature and up to pH 6. Antifungal activity has been observed in the bacterial cell-free supernatant, and the compounds have been identified as Phenyllactic acid (PLA), acetic acid and lactic acid. L. fermentum Lb-C-14 has the potential antifungal activity and could be suggested as a protective culture for the biopreservation of fermented foods.